2023
DOI: 10.1186/s12866-023-03135-x
|View full text |Cite
|
Sign up to set email alerts
|

Ligilactobacillus Salivarius improve body growth and anti-oxidation capacity of broiler chickens via regulation of the microbiota-gut-brain axis

Jiajun Yang,
Jing Wang,
Zongliang Liu
et al.

Abstract: Certain strains of probiotic bacteria can secret functional substances namely digestive enzymes and functional peptides to regulate physiological conditions such as digestion and anti-oxidation, which are often incorporated in industrial broiler chick production. However, few studies have detailed the action mechanisms and effects of these bacteria on regulating growth and anti-oxidation levels in broiler chickens. Ligilactobacillus salivarius is a strain of probiotic bacteria used as dietary supplement. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Ligilactobacillus salivarius was cultured and supplemented in the food of broiler chickens by Jiajun Yang to evaluate the effect of probiotics on growth through the modulation of gut microbial composition and its functional metabolites using metagenomic and metabolomic assays. They found that Ligilactobacillus salivarius optimized the microbial composition of the caecum of broilers [ 8 ]. Hailiang Yu used metagenomic and transcriptome sequencing techniques to identify microbiota and genes in the cecal contents and cecal tissue of infected (JS) and control (JC) chickens at day 4.5 post-infection, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ligilactobacillus salivarius was cultured and supplemented in the food of broiler chickens by Jiajun Yang to evaluate the effect of probiotics on growth through the modulation of gut microbial composition and its functional metabolites using metagenomic and metabolomic assays. They found that Ligilactobacillus salivarius optimized the microbial composition of the caecum of broilers [ 8 ]. Hailiang Yu used metagenomic and transcriptome sequencing techniques to identify microbiota and genes in the cecal contents and cecal tissue of infected (JS) and control (JC) chickens at day 4.5 post-infection, respectively.…”
Section: Introductionmentioning
confidence: 99%